Label-free analytical characterization of brazzein produced with the filamentous fungus Trichoderma reesei - Mojzita, Dominik; Aro, Nina; Kontturi, Juha; Kögler, Martin; Nordlund, Emilia; Hosia, Waltteri; Casteleijn, Marco G. (Frontiers in Bioengineering and Biotechnology, 2025)
Brazzein, a small, pH-stable, and heat-stable sweet protein, is a promising alternative to sucrose because of its extreme sweetness and stability. However, large-scale production through traditional extraction methods from plant sources is not economically feasible. To this end, the current study explores the production of recombinant brazzein in the filamentous fungus Trichoderma reesei using a synthetic expression system (SES) and the native fungal cbh1 promoter. Both methods successfully expressed brazzein in 24-well liquid cultures, with the SES-system achieving a production level of ∼1.3 g/L in bioreactor cultures. The protein was purified and characterized using SDS-PAGE, liquid chromatography high-content mass spectroscopy (LC-HCMS), Timegated™ Raman spectroscopy, dynamic light scattering (DLS), and nanoscale differential scanning fluorimetry (nanoDSF). The results confirmed that the correct folding and stability of brazzein attributed to its robust internal structure, demonstrating the potential of T. reesei as an efficient host for producing this sweet protein.